2015
DOI: 10.1038/srep09076
|View full text |Cite
|
Sign up to set email alerts
|

Different autosomes evolved into sex chromosomes in the sister genera of Salix and Populus

Abstract: Willows (Salix) and poplars (Populus) are dioecious plants in Salicaceae family. Sex chromosome in poplar genome was consistently reported to be associated with chromosome XIX. In contrast to poplar, this study revealed that chromosome XV was sex chromosome in willow. Previous studies revealed that both ZZ/ZW and XX/XY sex-determining systems could be present in some species of Populus. In this study, sex of S. suchowensis was found to be determined by the ZW system in which the female was the heterogametic ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
103
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(111 citation statements)
references
References 43 publications
7
103
1
Order By: Relevance
“…Recent studies on sex determination in S. viminalis and S. suchowensis showed that sex chromosomes are in the early stage of divergence, and sex is determined by the ZW system, with female being the heterogametic sex (Hou et al 2015, Pucholt et al 2015. However, the sex determination system may still be unsteady in this species because hermaphroditism occurs in different Salix species (Mirski 2014) and S. myrsinifolia individuals are even capable of changing sex during their life cycle (Mirski 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies on sex determination in S. viminalis and S. suchowensis showed that sex chromosomes are in the early stage of divergence, and sex is determined by the ZW system, with female being the heterogametic sex (Hou et al 2015, Pucholt et al 2015. However, the sex determination system may still be unsteady in this species because hermaphroditism occurs in different Salix species (Mirski 2014) and S. myrsinifolia individuals are even capable of changing sex during their life cycle (Mirski 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Although genetic maps show that sex determination in European Populus species is located further towards the centromere (Paolucci et al 2010;Tuskan et al 2012;Kersten et al 2014) and ongoing genomic work in P. trichocarpa continues to discover novel aspects of the sex determination system (Hou et al 2015;Geraldes et al 2015), this chromosome block was shown to present segregation distortion and reduced recombination in P. alba and P. tremula, as expected for an incipient sex chromosome (Macaya-Sanz et al 2011). The presence of a large NBS-LRR gene cluster may explain the evolution of this particular chromosome.…”
Section: R-genes and Sex Determinationmentioning
confidence: 99%
“…Recent studies of this chromosome have revealed different aspects of its complex history: different genomic architectures of sex determination depending on species (Geraldes et al 2015;Kersten et al 2014) but also a chromosome that is younger than the rest of the Populus genome with turnover events in the recent past (Geraldes et al 2015;Hou et al 2015). We discuss the potential roles of both R-genes and sex determination in shaping the genomic architecture of this chromosome.…”
Section: R-genes and Sex Determinationmentioning
confidence: 99%
“…Alström-Rapaport et al (1997) reported that under homogeneous environmental conditions, the sex ratio ranged from an extreme female bias to an extreme male bias in 13 full-sib families of Salix viminalis L. Their study suggested that S. viminalis gender determination followed a multilocus epistatic model. However, more recent studies have consistently shown that the sex of willow species, including S. viminalis, is governed by a single locus (Semerikov et al 2003;Hou et al 2015;Pucholt et al 2015). The sex of willows is determined by the ZW system in which the female is the heterogametic gender (Hou et al 2015;Pucholt et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent studies have consistently shown that the sex of willow species, including S. viminalis, is governed by a single locus (Semerikov et al 2003;Hou et al 2015;Pucholt et al 2015). The sex of willows is determined by the ZW system in which the female is the heterogametic gender (Hou et al 2015;Pucholt et al 2015). In most of the aforementioned studies, only a limited number of individuals were investigated.…”
Section: Introductionmentioning
confidence: 99%